A retrospective view of Costa Rican international trade over the last 30 years: Reflections on the implementation of public policies - Alonso Ubieta, Suyen (2025)
The objective of this essay is to reflect on trends in Costa Rican international trade, from the perspective of special and definitive regimes, and focus on the changes brought about in the national development model following public policy decisions. Marked growth in the export sector following the consolidation of the free trade zone regime, coupled with gaps in specialized human resource training and infrastructure quality, poses challenges to our country's international trade shortly. The conclusion is that although Costa Rica presents a successful model of global integration, vulnerabilities must be addressed through public policy.